The Rural Enlightenment of Johann Heinrich Voss - Robertson, R (Taylor and Francis, 2017)
Statements by Heine and Goethe show that they considered Voss a highly significant figure for German culture, as a model citizen and as an interpreter of Greek literature. In his socially critical idylls, Voss brought a new realism and a concern for liberty into German rural poetry, continued in his satire ‘Junker Kord’. Having produced much-admired translations of Homer, he adapted Homeric diction in his idyllic mock-epic Luise to depict harmonious domestic and social relations, in a way that deserves to be defended against imputations of Philistinism. Much later, he polemicized against the conversion to Catholicism of his old acquaintance Friedrich von Stolberg in a text that, though highly eccentric, attests his independence of mind.